A Phenomenological Investigation of Women's Experience of Recovering from Childhood Trauma and Subsequent Substance Abuse. Issue 1 (2nd January 2016) - Hunter, Ayesha C.
Abstract: Proceeding from a phenomenological perspective, the present study investigated the experiences of seven homeless women who had lived through childhood trauma and subsequent substance abuse, with specific focus on the recovery process experienced by each. Applying the analytical protocol of Giorgi (1985) to the written accounts obtained from the participants, 15 constituent themes of the recovery process were identified. In order to illuminate the participants' experiences with minimal influence of any possible researcher bias, the researcher refrained from labelling, judging or diagnosing the women's life circumstances. Consequently, no treatment paradigm was applied to help explain, predict or judge the behaviour of the participants during the course of this research.